Sociodemographic Profiles And Psychiatric Comorbidities Among Patients With Alcohol Dependence In Western Nepal (Journal of Psychiatrists' Association of Nepal, 2021)
Introduction: Alcohol is a potent drug that causes acute and chronic changes in almost all neurochemical systems and heavy drinking can produce serious temporary psychological symptoms including depression, anxiety and psychoses. Alcoholism is clinically heterogenous disorder with variable age of onset, drinking patterns, severity and comorbidity with other mental disorders. There is a gender difference in many aspect of alcohol use. The aim of the study was to study the sociodemographic profile, severity, gender difference and psychiatric comorbidities in patient with alcohol dependence syndrome in Nepalese population.Material And Method: This is a hospital based study done in patients coming to Nepalgunj Medical College, Kohalpur over a period of one year from June 2019 to May 2020 on consecutive serial basis. Diagnosis of alcohol dependence was made based on International Classification of Disease-10 (ICD-10) criteria. Semi structured proforma and Severity of Alcohol Dependence Questionnaire (SADQ) was applied in those patients and recorded accordingly. The data was analyzed using SPSS.Results: Out of 40 patients studied (N-40), 37 (92.5 %) were male and 3 (7.5 %) were female. Alcohol dependence is most common in the age bracket of 30-39 (43.1%) followed by 40-49 (33.4 %) with mean age of 40.3 years and the mean age of duration of alcohol use being 13.45 years. The mean amount of alcohol consumed per day is 92.25 grams. The SADQ scores, age of first alcohol use, duration of alcohol use in years and daily amount of alcohol use in grams is significantly different between male and female. Similarly there is severe alcohol dependence in 75 % while moderate level in 25 % of study population. Regarding psychiatric comorbidities, 90 % have comorbid other substance use disorder followed by anxiety disorders in 37.5 %, personality disorders in 35 %, mood disorders in 32.5 %, deliberate self harm in 30 % and psychotic disorders in 12.5 %.Conclusion: Alcohol dependence is most commonly found in young and adults of various age group. Age of first alcohol use, duration of alcohol use in years and daily amount of alcohol use in grams is significantly different between male and female. Alcohol dependence is comorbid with multiple psychiatric entities.